EVALUASI PROGRAM PADAT KARYA PRODUKTIF DALAM GERDU KEMPLING OLEH DINAS TENAGA KERJA DAN TRANSMIGRASI KOTA SEMARANG TAHUN 2011 - Muhammad Burhanudin Noor; Slamet Santoso; Dyah Lituhayu (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
The Government of Semarang through Perda No. 4 / 2008 about poverty reduction in Semarang City which is an acceleration in poverty reduction efforts. The strategy called Gerdu Kempling ( Integrated Health, Economy, Education, Infrastructure, and Environment ) and one of the program that is productive labor intensive by Dinas Tenaga Kerja dan Transmigrasi Kota Semarang. Productive Labor Intensive Program has been part of Gerdu Kempling starting in 2011 its in three locations: Village of Tanjung Mas, Mangunharjo, and Tugurejo. Evaluation of this program to see the performance on productive labor intensive programs will be viewed using criteria-criteria evaluation of policies according to William Dunn are: effectiveness, efficiency, sufficiency, alignment, responsiveness, accuracy. The barriers program that is viewed with a pattern which includes the planning, implementing, and controling.Productive labor intensive program performance in gerdu kempling Semarang City in 2011 where in this criteria evaluation, there are still 5 criteria judged not good, based on the effectiveness, efficiency, sufficiency, alignment, and accuracy activities. While good judgment only in criteria responsiveness activities. Barriers to programs such as provisioning and organizing where immature making activity stalled in the middle of the road. Lack of mentoring and controling is also a barrier to factor in this program.Overall many judgment that haven’t been good on these evaluation criteria, then program which have run this 2011 not been expressed successfully. Recommendations of this program, such as strengthening strategy and commitment of program implementor, using performance based budgets, the study of back numbers of the manpower, the need for intensive monitoring, as well as mentoring on group activities.